Biocompatibility of Amine‐Functionalized Silica Nanoparticles: The Role of Surface Coverage. Issue 10 (5th February 2019) - Hsiao, I‐Lun; Fritsch‐Decker, Susanne; Leidner, Arnold; Al‐Rawi, Marco; Hug, Vanessa; Diabaté, Silvia; Grage, Stephan L; Meffert, Matthias; Stoeger, Tobias; Gerthsen, Dagmar; Ulrich, Anne S.; Niemeyer, Christof M.; et al.
Abstract: Here, amorphous silica nanoparticles (NPs), one of the most abundant nanomaterials, are used as an example to illustrate the utmost importance of surface coverage by functional groups which critically determines biocompatibility. Silica NPs are functionalized with increasing amounts of amino groups, and the number of surface exposed groups is quantified and characterized by detailed NMR and fluorescamine binding studies. Subsequent biocompatibility studies in the absence of serum demonstrate that, irrespective of surface modification, both plain and amine‐modified silica NPs trigger cell death in RAW 264.7 macrophages. The in vitro results can be confirmed in vivo and are predictive for the inflammatory potential in murine lungs. In the presence of serum proteins, on the other hand, a replacement of only 10% of surface‐active silanol groups by amines is sufficient to suppress cytotoxicity, emphasizing the relevance of exposure conditions. Mechanistic investigations identify a key role of lysosomal injury for cytotoxicity only in the presence, but not in the absence, of serum proteins. In conclusion, this work shows the critical need to rigorously characterize the surface coverage of NPs by their constituent functional groups, as well as the impact of serum, to reliably establish quantitative nanostructure activity relationships and develop safe nanomaterials. Abstract : The critical role of surface coverage by functional groups for the biocompatibility of nanoparticles is assessed. Silica nanoparticles are modified with amino groups and the extent of surface coverage is analyzed and quantified. While in the absence of serum (‐corona) silica nanoparticles are cytotoxic irrespective of surface modification. In the presence of serum, amine‐functionalized but not plain silica nanoparticles appear biocompatible.